2017
DOI: 10.1002/adma.201700291
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Solution Phase Growth of Transition Metal Dichalcogenide Thin Films Directly on Solid Substrates

Abstract: Ultrathin transition metal dichalcogenides (TMDs) have exotic electronic properties. With success in easy synthesis of high quality TMD thin films, the potential applications will become more viable in electronics, optics, energy storage, and catalysis. Synthesis of TMD thin films has been mostly performed in vacuum or by thermolysis. So far, there is no solution phase synthesis to produce large-area thin films directly on target substrates. Here, this paper reports a one-step quick synthesis (within 45-90 s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 35 publications
0
50
0
Order By: Relevance
“…Currently, the materials reported are mostly TMDCs (MoS 2 , WS 2 , MoSe 2 , WSe 2 and Mo x W 2− x S 2 , etc. ) and PTMCs (SnS 2− x Se x , CuInSe 2 , In 2 Se 3 , etc.) .…”
Section: Structures Of 2d Metal Chalcogenide Thin Filmsmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, the materials reported are mostly TMDCs (MoS 2 , WS 2 , MoSe 2 , WSe 2 and Mo x W 2− x S 2 , etc. ) and PTMCs (SnS 2− x Se x , CuInSe 2 , In 2 Se 3 , etc.) .…”
Section: Structures Of 2d Metal Chalcogenide Thin Filmsmentioning
confidence: 99%
“…If a one‐step thin film growth is possible it will provide genuine advantage of the solution‐phase growth such as low‐temperature synthesis, versatile scale‐up into massive amount, rich chemistry during the synthesis, and possibility of all‐in‐one printed production. In a very recent study, Jeong and co‐workers demonstrated a one‐step synthesis of metal chalcogenide thin films (MoS 2 , MoSe 2 , WS 2 , WSe 2 ) in a solution phase directly on Si substrates . They adopted the microwave‐assisted crystal growth.…”
Section: Synthesis Of Metal Chalcogenide Thin Films By the Compound Fmentioning
confidence: 99%
See 3 more Smart Citations